P50 Changing use of CT pulmonary angiography in a uk tertiary hospital over a 6-year period. (15th November 2016) - Ratnakumar, R; Corcoran, JP; Talwar, A; Hallifax, RJ; Psallidas, I; Wrightson, JM; Gleeson, FV; Rahman, NM
Abstract : Background: CT pulmonary angiography (CTPA) is widely regarded as the gold standard test for suspected pulmonary embolism (PE) and is increasingly used as an all-inclusive diagnostic tool for patients with symptoms of acute cardio-respiratory pathology. This has led to an increase in the number of CTPA scans, but no clear reduction in mortality from pulmonary embolic disease. CTPA may be of benefit in making other clinically significant (non-PE) diagnoses, but increased use of CTPA has resource and ionising radiation implications. Method: We reviewed records of patients undergoing CTPA in our centre during the same 6-week reference period in each year from 2009 to 2014 to ascertain the number of scans positive for PE and/or other diagnoses. The clinical relevance of "other diagnoses" was evaluated, as well as whether "other diagnoses" were evident on earlier investigations such as chest X-ray. Results: Patient records associated with 1882 scans were reviewed. The use of CTPA increased by two-thirds over the 6-year study period, with the likelihood of acute PE being diagnosed remaining unchanged (Table 1 ). Other diagnoses were seen on more than 80% of scans; the majority were either not therapeutically relevant or potentially evident from previous investigations. Conclusion: Our evaluation of experience in a stable population has demonstrated increased use of CTPA scanning with no change in the diagnostic yield for acute PE. The percentage of patients with additional abnormalities has remained stable, implying the population under investigation is similar. It is uncertain if the increase in the incidence of PE is due to detection of previously undetected emboli, and whether increasing use has reduced mortality from PE. Findings also confirm significant use to screen for other causative pathology. Further work should assess the character of the emboli and the overall impact on morbidity and mortality from increasing CTPA use.